TOXIC BEAUTY STANDARDS REFLECTED IN PRAKASA’S IMPERFECT: A PSYCHOANALYSIS - Citra Nareswara Pramesti; Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2022)
ABSTRACT Imperfect is a movie depicting the struggle of someone who is obsessed with toxic beauty standards. The researcher applies psychoanalysis theory which especially related to id, ego and superego discovered by Freud (1923). The purpose of this study is to find out what causes the main character of this movie to be obsessed with toxic beauty standards and to find out the experiences id, ego and superego which is related to her life. The data from this study were obtained from watching and analyzing the movie Imperfect. After analyzing this film, it can be said that the basis of beauty standard is neutral, corresponds to each individual's preferences in what they see as beautiful. However, the fixation on beauty standards could become toxic if one cannot let go of their obsession with the flaws that are visible on their body. Body neutrality movement arises to tackle this problem. It invites people not to put their focus on the aesthetics of their bodies, instead people should put their focus on the functionality of their limbs. Keywords: Movie Imperfect, Psychoanalysis, Toxic Beauty Standard, Body Neutrality